Survival Analysis in Pediatric Osteosarcoma - Mururul Aisyi; Ayu Hutami Syarif; Nur Asih Anggraeni; Adhitya Bayu Perdana; Hutomo Rezky; Agus Kosasih; Achmad Basuki (Indonesian Journal of Cancer, 2019)
Background: Osteosarcoma is the most common bone malignancy in childhood and adolescence. Despite significant advances in diagnostic and therapeutic modalities, osteosarcoma has generally poor prognosis. Several studies highlighted the prognostic significance of demographic and clinical parameters in the pediatric population. Controversy exists about which obvious factors of mortality in some institutions. Meanwhile, little is known about the overall survival (OS) of pediatric osteosarcoma in Dharmais Cancer Hospital.The aim of this study is to estimate the OS in pediatric osteosarcoma.Methods: This retrospective cohort study enrolled 41 children with osteosarcoma during the period of January 2010-September 2017. Patients were selected using inclusion and exclusion criteria. Overall survival (OS) and patient variables were plotted using Kaplan-Meier.Results: Our result showed that all patients admitted to our hospital in advanced stages (IIB and III). Their median OS was 23 months (12.3-33.7 months) with the survival probability was 29.4%.Conclusions: Median OS of pediatric osteosarcoma in our institution was 23 months and the survival probability was 29.4%. It can be used as evidence showing lack of cancer awareness and early detection in our country.